Exposing Existing Fallacies Regarding the Captancies in the Bosnian Frontier Area between the 16th-18th Centuries - Moačanin, Nenad (Array, 2000)
Two major extreme views on Bosnian border militia in the 18th . early 19th c. are currently popular. The local one argues that the militia struggled for national independence, while the international one insists on harmony and shared interests of the Sublime Porte and the militia. The present article demonstrates the essential weakness of both.